Pembelajaran Terjemah Berbasis Produk “Studi Kasus Pembelajaran Terjemah Mahasiswa UIN Raden Fatah Palembang Di Markaz Lisan Arabi Singosari-Malang” - Miftahul Huda (CV. Satria Jaya, 2023)
Learning translation based on product is learning translation found in the Markaz Lisan Arabic Singosari-Malang and is used when there are students who want to learn about translation. The purpose of conducting this research is to describe the process of learning translation based on Arabic products into Indonesian, and the strengths and weaknesses of learning translation based on products in order to produce sales-worthy translation books. To obtain this description, a qualitative research was conducted. This type of research includes case study research. This research can also be said to be a descriptive study that aims to collect data and describe it thoroughly in accordance with the problem to be solved. Sources of data in this study are: 1) Primary data sources, namely director of Markaz Lisan Arabic, teacher of Markaz Lisan Arabic, admin of Markaz Lisan Arabic, head of marketing of Lisan Arabic. 2) Secondary data sources, namely in the form of documents. To be able to obtain the data needed, this study uses several methods, namely observation, interviews and documentation. The results of this study indicate that the learning translation based on product process has several stages, these stages are: 1) the test phase, 2) the translation process stage, 3) the translation result collection stage. The advantages of learning translation based on product in Markaz Lisan Arabic 1) Teacher Markaz Lisan Arabic, 2) Publishing facilities, 3) Students can read and translate source languages, 4) Increase student knowledge about translation 5) increase student knowledge about the world of literacy. Whereas the weaknesses of learning translation based on product at the Markaz Lisan Arabic 1) The lack of learning translation facilities, 2) The short process of learning translation, 3) Learning translation at the Markaz Lisan Arabic is only suitable for the student level.